Entre evidências e conceitos. Plantas e animais nos estudos neolíticos em Portugal - Carvalho, António Faustino (Estudos Arqueológicos de Oeiras, 2020)
The analysis of reference works allows us to identify three main phases in the study of subsistence practices in the Neolithic of Portugal. In a first, from the mid-nineteenth century, the “three age system” is assimilated but the issues of subsistence do not enter into the concerns of the authors (Pereira da Costa, Gabriel Pereira). Between the end of that century and the middle of the twentieth century, there was a rapid introduction of the correlation Neolithic = agriculture and pastoralism (Carlos Ribeiro, Augusto Filipe Simões), which however disappears through time. Finally, between the 1940s and 80s, V. G. Childe’s proposal for a “Neolithic revolution” does not penetrate Portuguese research; the perception that the Neolithic was essentially characterized by pastoral practices will predominate (Georg and Vera Leisner).